2020
DOI: 10.17219/acem/130603
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes for acute respiratory failure in coronavirus disease 2019: An observational cohort study

Abstract: Background. The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread throughout Europe. However, there is a lack of data on the full clinical course of patients infected with SARS-CoV-2 in Europe, especially in the population that developed acute respiratory failure (ARF).Objectives. To identify risk factors associated with developing ARF during SARS-CoV-2 infection. Materials and methods.This was an observational study of 60 adult patients with laboratory-confirmed SARS-CoV-2 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…High mortality observed in the second study may be associated with delayed intubation due to the use of HFNOT, as compared to passive oxygen therapy. Another Polish observational study revealed that mortality among patients with acute respiratory failure and baseline oxygenation index ≤ 300 mmHg was 32%; however, mortality in a subgroup of patients requiring invasive mechanical ventilation reached 66.7% and was markedly higher compared to our cohort [9]. Unfortunately, the lack of detailed data on patients transferred to the ICU makes it impossible to confirm a relationship between the clinical characteristics of patients and treatment outcomes.…”
Section: Characteristicscontrasting
confidence: 75%
“…High mortality observed in the second study may be associated with delayed intubation due to the use of HFNOT, as compared to passive oxygen therapy. Another Polish observational study revealed that mortality among patients with acute respiratory failure and baseline oxygenation index ≤ 300 mmHg was 32%; however, mortality in a subgroup of patients requiring invasive mechanical ventilation reached 66.7% and was markedly higher compared to our cohort [9]. Unfortunately, the lack of detailed data on patients transferred to the ICU makes it impossible to confirm a relationship between the clinical characteristics of patients and treatment outcomes.…”
Section: Characteristicscontrasting
confidence: 75%
“…An increased NLR at hospital admission is emerging as a useful indicator of disease severity and a potential tool of diagnostic and prognostic utility (106,107). For example, significantly higher baseline NLR values have been measured in COVID-19 patients who develop severe/critical disease when compared to mild or moderate cases (51,90,92,95,(108)(109)(110)(111), with this elevation persisting for up to 15 days post-hospital admission (51,100,112). In terms of its discriminatory power, NLR has been shown to distinguish severe COVID-19 patients from non-severe cases with a level of accuracy considered fair to good based on AUROC values (95,100,107,109,112,113).…”
Section: Non-human Primatesmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is a newly emerged infectious disease first identified in December 2019. The major clinical features of COVID-19 include fever, shortness of breath, cough, headache, and fatigue, which can lead to severe pneumonia, lung injury, acute respiratory/multiorgan failure, and death [ 1 4 ]. A variety of risk factors, including older age, hypertension, obesity, diabetes mellitus, and cardiovascular comorbidities, are associated with COVID-19 [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%